Burkholderia pseudomallei multi-centre study to establish EUCAST MIC and zone diameter distributions and epidemiological cut-off values. (May 2021) - Karatuna, O.; Dance, D.A.B.; Matuschek, E.; Åhman, J.; Turner, P.; Hopkins, J.; Amornchai, P.; Wuthiekanun, V.; Cusack, T.-P.; Baird, R.; Hennessy, J.; Norton, R.; et al.
Abstract: Objectives: Melioidosis, caused by Burkholderia pseudomallei, requires intensive antimicrobial treatment. However, standardized antimicrobial susceptibility testing (AST) methodology based on modern principles for determining breakpoints and ascertaining performance of methods are lacking for B. pseudomallei . This study aimed to establish MIC and zone diameter distributions on which to set epidemiological cut-off (ECOFF) values for B. pseudomallei using standard EUCAST methodology for non-fastidious organisms. Methods: Non-consecutive, non-duplicate clinical B. pseudomallei isolates (9–70 per centre) were tested at eight study centres against eight antimicrobials by broth microdilution (BMD) and the EUCAST disc diffusion method. Isolates without and with suspected resistance mechanisms were deliberately selected. The EUCAST Development Laboratory ensured the quality of study materials, and provided guidance on performance of the tests and interpretation of results. Aggregated results were analysed according to EUCAST recommendations to determine ECOFFs. Results: MIC and zone diameter distributions were generated using BMD and disc diffusion results obtained for 361 B. pseudomallei isolates. MIC and zone diameter ECOFFs (mg/L; mm) were determined for amoxicillin-clavulanic acid (8; 22), ceftazidime (8; 22), imipenem (2; 29), meropenem (2; 26), doxycycline (2; none), tetracycline (8; 23), chloramphenicol (8; 22) and trimethoprim-sulfamethoxazole (4; 28). Conclusions: We have validated the use of standard BMD and disc diffusion methodology for AST of B. pseudomallei . The MIC and zone diameter distributions generated in this study allowed us to establish MIC and zone diameter ECOFFs for the antimicrobials studied. These ECOFFs served as background data for EUCAST to set clinical MIC and zone diameter breakpoints for B. pseudomallei .